2013
DOI: 10.1590/s0100-67622013000200010
|View full text |Cite
|
Sign up to set email alerts
|

Sucesso reprodutivo de espécies distílicas de psychotria (rubiaceae) em sub-bosque de floresta atlântica

Abstract: Sucesso reprodutivo de espécies distílicas de Psychotria... SUCESSO REPRODUTIVO DE ESPÉCIES DISTÍLICAS DE REPRODUCTIVE SUCCESS OF DISTYLOUS SPECIES OF Psychotria (RUBIACEAE) OF UNDERSTORY ATLANTIC FOREST

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The >80 % viability of pollen grains, a common characteristic of heterostylic species, has also been recorded in P. poeppigiana (Coelho & Barbosa 2004), P. barbiflora (Teixeira & Machado 2004), P. carthagenensis (Koch et al 2010), P. conjugens, P. sessilis, P. hastisepala (Silva & Vieira 2013), and P. elata (Silva & Segura 2015). This may assist in the reproductive success of the species (Valois-Cuesta et al 2012).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The >80 % viability of pollen grains, a common characteristic of heterostylic species, has also been recorded in P. poeppigiana (Coelho & Barbosa 2004), P. barbiflora (Teixeira & Machado 2004), P. carthagenensis (Koch et al 2010), P. conjugens, P. sessilis, P. hastisepala (Silva & Vieira 2013), and P. elata (Silva & Segura 2015). This may assist in the reproductive success of the species (Valois-Cuesta et al 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Habitat loss was observed inside and around the forest fragments studied, which was aggravated by the proximity of large agricultural areas, traces of logging and hunting, openings of clearings, and the presence of animals as cattle (personal observation). Habitat loss was one of the reasons for the low genetic diversity observed in natural populations of Psychotria hastisepala in the state of Minas Gerais (Silva & Vieira 2013). In addition, habitat loss diminishes the areas of clusters, and can cause an imbalance in the ratio between morphs (anisoplethy), as well as reducing the number of physiologically mature plants for reproduction (Silva & Segura 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One result of this preference for longstyled flowers is the deposition of incompatible pollen, resulting in stigma occlusion, preventing the compatible grains from germinating (GANDERS, 1979), affecting the fruiting of the morph in question. Indeed, in the study area, the long-styled flowers of P. conjungens and, mainly, of P. hastisepala produced lower fruit set than the obtained in short-styled flowers VIEIRA, 2013;SILVA et al, 2014) Among the pollinator bees of the studied Psychotria species, Ariphanarthra palpalis was a common pollinator. This species is solitary, restricted to the forest interior, active in the early morning hours and on cloudy days.…”
Section: Discussionmentioning
confidence: 87%
“…In a study of the reproductive biology of 21 species of Psychotria on Barro Colorado Island, Sakai and Wright (2008) [37] compared data from phylogenetic information of the genus, and found that changes in the morphological characteristics of distyly are associated with the weakening of incompatibility, and monomorphism and homostyly that evolved independently in the genus as a result of low population density and limited availability of pollen. Pollen limitation has been related to the formation of one-seeded fruits in distylous species of Palicourea [38] and Psychotria [20] [39]. The formation of seedless fruits was recorded in Palicourea lassiolaris [40] and P. longepedunculata [38].…”
Section: Discussionmentioning
confidence: 99%